2019
DOI: 10.3390/ijerph16224474
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cancer for Workers Exposed to Antimony Compounds: A Systematic Review

Abstract: Background: Antimony (Sb) trioxide and antimony trisulfide are “2B: Possibly carcinogenic to humans” and “3: Unclassifiable” according to the International Agency for Research on Cancer (IARC). The U.S. National Toxicology Program (NTP) concluded that antimony trioxide “is reasonably anticipated to be a human carcinogen based on studies in rats and mice”. We investigated the cancer hazard of antimony compounds for workers, a population with high exposure to antimony substances. Methods: Using the “Guidelines f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…The side effects of heavy metals have been widely reported, such as V has a toxic impact on the human digestive system, blood, nervous system and immune system (Chlubek et al, 2012;Rawal et al, 1997). Sb may cause discomforts such as nausea, vomiting, anorexia, abdominal pain and gastric ulcer (Saerens et al, 2019;Sundar & Chakravarty, 2010). Moreover, excessive As intake may cause cancers (liver cancer, lung cancer, bladder cancer) and other side effects (hypertension, neuropathy, diabetes, tibial disease) (Wu et al, 2009b;Xu & Wang, 2020).…”
Section: Human Health Risk Assessmentmentioning
confidence: 99%
“…The side effects of heavy metals have been widely reported, such as V has a toxic impact on the human digestive system, blood, nervous system and immune system (Chlubek et al, 2012;Rawal et al, 1997). Sb may cause discomforts such as nausea, vomiting, anorexia, abdominal pain and gastric ulcer (Saerens et al, 2019;Sundar & Chakravarty, 2010). Moreover, excessive As intake may cause cancers (liver cancer, lung cancer, bladder cancer) and other side effects (hypertension, neuropathy, diabetes, tibial disease) (Wu et al, 2009b;Xu & Wang, 2020).…”
Section: Human Health Risk Assessmentmentioning
confidence: 99%
“…As mentioned above, an ingestion of Sb by humans can cause a variety of disorders, such as irritation of the eyes, severe vomiting, diarrhea, skin lesions, lung diseases, heart problems, stomach ulcers [67,70] and different types of cancers, including PCa [31][32][33][34]. In spite of a significant correlations between Sb exposure and the risk of PCa have been There are some limitations in our study, which need to be taken into consideration when interpreting the results of this review.…”
Section: All Natural Chemical Elements Of the Periodicmentioning
confidence: 99%
“…Furthermore, experimental and epidemiological data identified that Sb compounds should be considered as genotoxic carcinogens [30][31][32][33][34]. Consequently, the International Agency for Research on Cancer (IARC) has evaluated Sb as possibly carcinogenic to humans (Group 2B) [35].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations